Reporting quality of qualitative health studies published by Peruvian authors: A scoping review - Cristhian Rojas-Miliano; Andrea Dámaso-Román; Guillermo Almeida-Huanca; Nikol Mayo-Puchoc; Yolanda Viguria-Chavez; Andy Rick Sánchez-Villena; Alvaro Taype-Rondan; Rubí Paredes-Angeles (PLoS ONE, 2026)
Qualitative research offers valuable insights into complex social and behavioral processes in the health sciences; however, its contribution depends on the quality and transparency of reporting. This scoping review aimed to describe the methodological characteristics and reporting quality of qualitative studies published by Peruvian authors between 2022 and 2025. Following Prisma-scr guidelines, a systematic search was conducted in SCOPUS, and reporting quality was assessed using the Standards for Reporting Qualitative Research (SRQR) tool. A total of 147 qualitative studies were included. Most were published in English (49.0%), had a median of five authors; 71.4% had a first author affiliated with a Peruvian institution, and 58.5% involved exclusively Peruvian authors. Studies were mainly conducted in Lima (50.3%). Ethics committee approval was not reported in 24.5% of studies, and 40.8% did not provide an ethics approval code. Adherence to SRQR items was highest for abstracts (95.9%), study purpose (95.2%), and presentation of findings (93.9%), whereas reporting of title elements (31.3%), qualitative approach (49.0%), and researcher reflexivity (37.4%) was limited. Publication in Spanish and Peruvian first authorship were associated with lower SRQR scores, whereas a higher number of authors and international collaboration were associated with higher scores. Overall, qualitative studies published by Peruvian authors showed variable reporting quality, with important methodological and ethical aspects frequently under reported, highlighting the need to strengthen reporting practices, particularly for core qualitative components.